The Vacuolar Pathway in Macrophages Plays a Major Role in Antigen Cross-Presentation Induced by the Pore-Forming Protein Sticholysin II Encapsulated Into Liposomes - Cruz-Leal, Yoelys; Grubaugh, Daniel; Nogueira, Catarina V.; Lopetegui-González, Isbel; del Valle, Anaixis; Escalona, Felipe; Laborde, Rady J.; Alvarez, Carlos; Fernández, Luis E.; Starnbach, Michael N.; Higgins, Darren E.; Lanio, María E. (Frontiers in Immunology, 2018)
Cross-presentation is an important mechanism for the differentiation of effector cytotoxic T lymphocytes (CTL) from naïve CD8+ T-cells, a key response for the clearance of intracellular pathogens and tumors. The liposomal co-encapsulation of the pore-forming protein sticholysin II (StII) with ovalbumin (OVA) (Lp/OVA/StII) induces a powerful OVA-specific CTL activation and an anti-tumor response in vivo. However, the pathway through which the StII contained in this preparation is able to induce antigen cross-presentation and the type of professional antigen presenting cells (APCs) involved have not been elucidated. Here, the ability of mouse bone marrow-derived dendritic cells (BM-DCs) and macrophages (BM-MΦs) stimulated with Lp/OVA/StII to activate SIINFEKL-specific B3Z CD8+ T cells was evaluated in the presence of selected inhibitors. BM-MΦs, but not BM-DCs were able to induce SIINFEKL-specific B3Z CD8+ T cell activation upon stimulation with Lp/OVA/StII. The cross-presentation of OVA was markedly decreased by the lysosome protease inhibitors, leupeptin and cathepsin general inhibitor, while it was unaffected by the proteasome inhibitor epoxomicin. This process was also significantly reduced by phagocytosis and Golgi apparatus function inhibitors, cytochalasin D and brefeldin A, respectively. These results are consistent with the concept that BM-MΦs internalize these liposomes through a phagocytic mechanism resulting in the cross-presentation of the encapsulated OVA by the vacuolar pathway. The contribution of macrophages to the CTL response induced by Lp/OVA/StII in vivo was determined by depleting macrophages with clodronate-containing liposomes. CTL induction was almost completely abrogated in mice depleted of macrophages, demonstrating the relevance of these APCs in the antigen cross-presentation induced by this formulation.